2021
DOI: 10.1007/s11218-021-09621-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding procrastination: A case of a study skills course

Abstract: Procrastination is consistently viewed as problematic to academic success and students’ general well-being. There are prevailing questions regarding the underlying and maintaining mechanisms of procrastination which are yet to be learnt. The aim of the present study was to combine different ways to explain procrastination and explore how students’ time and effort management skills, psychological flexibility and academic self-efficacy are connected to procrastination as they have been commonly addressed separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 73 publications
2
33
0
5
Order By: Relevance
“…As predicted on Hypothesis 2, self-regulation is associated and positively predicts self-efficacy and achievement, contrary to procrastination. These results have been widely evidenced in college students [37,61,[91][92][93][94] and are also present in high school students. For that reason, due to the recent rise in virtual education for primary and high school students, it is essential to guide students to plan adequate knowledge acquisition goals and strategies of self-learning [95].…”
Section: Hypothesis Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…As predicted on Hypothesis 2, self-regulation is associated and positively predicts self-efficacy and achievement, contrary to procrastination. These results have been widely evidenced in college students [37,61,[91][92][93][94] and are also present in high school students. For that reason, due to the recent rise in virtual education for primary and high school students, it is essential to guide students to plan adequate knowledge acquisition goals and strategies of self-learning [95].…”
Section: Hypothesis Discussionmentioning
confidence: 54%
“…That way, those who possess self-regulation and control skills choose adequate behavioral adjustment strategies, self-control the development of their working schedule looking to respond appropriately to their tasks to improve their performance [8,30]. The self-regulation general variable is present in the promotion of motivational-affective strategies [28,29]; the type of assumed learning scope [31][32][33]; achievement emotions [34,35]; coping strategies [36]; academic confidence and procrastination [37]. Contrary to selfregulation, when a dys-regulatory behavior as procrastination is present [26,27], people decide to postpone actions regardless of their adverse effects, increasing the perceived stress level, affecting important adjustment behaviors.…”
Section: Students' Factors Of Regulation: Self-regulation Procrastination and Academic Self-efficacymentioning
confidence: 99%
“…Academic procrastination is considered problematic to academic success and a self-regulated failure among university students (Zhang et al, 2018 ; Hailikari et al, 2021 ). It is necessary to study the trend of academic procrastination comprehensively to manage to reduce it.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that psychological flexibility has a strong relationship to progression in studying (Asikainen, 2018;Asikainen et al, 2018) and a negative relationship to problems in studying (Levin et al, 2018) and procrastination (Glick et al, 2014). In addition, psychological flexibility together with organized studying have also been found to be negatively related to procrastination (Hailikari et al, 2021), and thus, by combining these two in this course may have influenced students' experiences of more motivating and more efficient studying as the students reflected in their journals. Based on the reflections of the students, we suggest that supporting both psychological flexibility and study skills can have positive effects on students' well-being and study skills.…”
mentioning
confidence: 91%